Voices from far away lands : from divergent to convergent - Saudelli, Mary Gene; Kusch, James; Carroll, Sharon (Cambridge Scholars Publishing, 2019)
This collection of essays highlights the power of the story, especially as told by those living an international life. What compels them to share their experiences? What have they experienced? What have they learned? In this time of tensions across the globe, rapid technological change and extensive migration, there is compelling value in learning through storied experiences. This volume explores the concepts of identity, change, equality, ethics, citizenship, family, feminism, community, faiths and values, advocacy and charity, systems, and languages. These movements are contextualized through a storied approach, adopting social exchange theory, identity theory, and globalization and internationalization movements as frameworks. This book will appeal to academics, ethnographers, practitioners, graduate students, educators, and researchers.